(3TQM gOGjI GdCHgQjs - (3GdMSjfj GdnerjnHPj, bGVj ejQ, MSjf Hf eYjf GdOjf, J (B910 (3g`s
(3ChdgG (B:s
(3HSe Gddg deG QCjJ ceGd Yjf GdCYjGf hgh fhY GdEfSGf HGdGQJbGA Edi CYdGe GdaWfI hGdGgJOGA Edi CbSGe GdMceI EP HgG jUjQ GdfGXQ aj MbGFb GdCTjGA HUjQG hefg jDJi GdMceIs
(3BNQgG (B:s
(3hfbhd CjVG GddjaGJ GdYfUQjI RGjOI Ydi GdUhQ GdWHjYjI dGfgG JSJMjd aj GdcjajGJ eKd GdJSNf hGdJHQO eY HbGA GdUhQI GdWHjYjI HPhGJg eG PcQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 260s
(3cTa GdXfhf (B2 / 2029s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs